2020
DOI: 10.3390/f11121282
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cultivation of Fruit Plantations Decreases Mineralization and Nitrification Rates in Calcareous Soil in the Karst Region in Southwestern China

Abstract: Determination of rates of mineralization of organic nitrogen (N) into ammonium-N (NH4+-N) and nitrification of NH4+-N into nitrate-N (NO3−-N) could be used to evaluate inorganic N supply capacity, which, in turn, could guide N fertilizer application practices in crop cultivation systems. However, little information is available on the change of mineralization and nitrification in soils under fruit cultivation systems converted from forestlands in karst regions. In a 15N-tracing study, inorganic N supply capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…The gross mineralization and nitrification rates were quantified using 15 N pool dilution techniques [14,35,36]. A series of 30 g samples of fresh soil (oven-dried) were weighted into 250 mL Erlenmeyer flasks for each soil, and these were subsequently pre-incubated at 25 • C for 24 h. After the pre-incubation, 1 mL of 15 NH 4 NO 3 or NH 4 15 NO 3 (10 atom% 15 N excess) solution, containing 1.5 mg NH 4 + -N kg -1 and 1.5 mg NO 3 − -N kg -1 , was evenly applied to the soil in each Erlenmeyer flask. Noticeably, the amount of applied NH 4 NO 3 was relatively higher in this study compared to that previously reported [14,32].…”
Section: Gross Mineralization and Nitrification Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…The gross mineralization and nitrification rates were quantified using 15 N pool dilution techniques [14,35,36]. A series of 30 g samples of fresh soil (oven-dried) were weighted into 250 mL Erlenmeyer flasks for each soil, and these were subsequently pre-incubated at 25 • C for 24 h. After the pre-incubation, 1 mL of 15 NH 4 NO 3 or NH 4 15 NO 3 (10 atom% 15 N excess) solution, containing 1.5 mg NH 4 + -N kg -1 and 1.5 mg NO 3 − -N kg -1 , was evenly applied to the soil in each Erlenmeyer flask. Noticeably, the amount of applied NH 4 NO 3 was relatively higher in this study compared to that previously reported [14,32].…”
Section: Gross Mineralization and Nitrification Ratesmentioning
confidence: 99%
“…In soil, inorganic N is produced mainly through the conversion of organic N to NH 4 + (i.e., mineralization) and the subsequent oxidation of NH 4 + to NO 3 -(i.e., nitrification) [11][12][13]. Thus, the determination of gross mineralization and nitrification rates using the 15 N dilution technique can provide a better understanding of the process and intensity of inorganic N production, which has been widely conducted in various ecosystems (e.g., forest, agriculture, grass) [14][15][16]. However, the relevant information regarding changes in gross mineralization and nitrification is limited for banana plantations in tropical or subtropical regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen (N) is a limiting factor for the growth and development of plants as well as a robust indicator of soil fertility [1,2]. In terrestrial ecosystems, N mainly exists in organic forms in which its availability is restricted by its chemical composition and structure [3].…”
Section: Introductionmentioning
confidence: 99%